Funções Base Especiais para a Solução de Problemas de Espalhamento Eletromagnético por Corpos de RevoluçãoDOI: 10.14209/jcis.1998.5 - Lisboa Teixeira, Fernando Casimiro; Ricardo Bergmann, José (Journal of Communication and Information Systems, 2015)
The use of special base functions is investigated in the solution of integral equations by the Method of Moments far the analysis of electromagnetic scattering produced by perfectly conducting objects with circular symmetry. Performance with respect to relative precision and computational requirements for two classes of functions (B-spline and band-limited) is evaluated in comparison with that achieved by local and global trigonometric functions. In particular, behavior caused by near-edge induced currents is investigated. Also considered are issues related to spatial and spectral localization of base functions. Examples are given which include scattering by reflector antennas.